2021
DOI: 10.1186/s13049-021-00938-7
|View full text |Cite
|
Sign up to set email alerts
|

Discharge from the trauma centre: exposure to opioids, unmet information needs and lack of follow up—a qualitative study among physical trauma survivors

Abstract: Background Physical trauma is associated with mortality, long-term pain and morbidity. Effective pain management is fundamental in trauma care and opioids are indispensable for treating acute pain; however, the use and misuse of prescribed opioids is an escalating problem. Despite this, few studies have been directed towards trauma patients in an early phase of rehabilitation with focusing on experiences and perspectives of health and recovery including pain and persistent use of prescribed opi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…A recent study interviewing 13 patients with orthopedic trauma identified the theme of insecurity after discharge due to unmet information needs about their injury and its expected effect on their physical function, about the psychological reaction to trauma, and about opioid side effects and tapering. 26 These patients also noted lack of follow-up after discharge from the trauma center as a concern. Zatzick et al tested two models of care seeking to improve the postdischarge experience of patients with trauma—identification of patient concerns prior to discharge followed by either a care management program or nurse notification of the concerns.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study interviewing 13 patients with orthopedic trauma identified the theme of insecurity after discharge due to unmet information needs about their injury and its expected effect on their physical function, about the psychological reaction to trauma, and about opioid side effects and tapering. 26 These patients also noted lack of follow-up after discharge from the trauma center as a concern. Zatzick et al tested two models of care seeking to improve the postdischarge experience of patients with trauma—identification of patient concerns prior to discharge followed by either a care management program or nurse notification of the concerns.…”
Section: Discussionmentioning
confidence: 95%
“…These findings contribute to a scarce literature about the experience of patients with trauma in the inpatient to outpatient care transition. A recent study interviewing 13 patients with orthopedic trauma identified the theme of insecurity after discharge due to unmet information needs about their injury and its expected effect on their physical function, about the psychological reaction to trauma, and about opioid side effects and tapering 26. These patients also noted lack of follow-up after discharge from the trauma center as a concern.…”
Section: Discussionmentioning
confidence: 99%
“…While nearly 1.3 million people suffer a fatal outcome from road traffic accidents every year, between 20 and 50 million individuals survive and live with permanent or temporary disabilities 3. Furthermore, as medical technology and trauma system improvements have reduced trauma-related mortality,4 5 an increased interest has been directed towards injury survivors and the challenges they experience following hospital discharge 6–9…”
Section: Introductionmentioning
confidence: 99%
“…Major trauma survivors face many challenges as they recover, including persisting pain, disability, financial stress, social difficulties, and poor mental health. [1][2][3][4][5][6][7] While many patients eventually retain a near baseline level of function, other patients are plagued by ongoing and complex psychosocial and physical challenges that can disrupt their life for years after injury, leading some to suggest that major trauma be considered a chronic disease. 8,9 Little is known about the psychosocial recovery trajectories of major trauma survivors.…”
mentioning
confidence: 99%
“…Although nearly 87% of patients who experience a major injury survive, the patient's recovery is often far from over at hospital discharge. Major trauma survivors face many challenges as they recover, including persisting pain, disability, financial stress, social difficulties, and poor mental health 1–7 . While many patients eventually retain a near baseline level of function, other patients are plagued by ongoing and complex psychosocial and physical challenges that can disrupt their life for years after injury, leading some to suggest that major trauma be considered a chronic disease 8,9 …”
mentioning
confidence: 99%